(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
A small number of poems by the English poet Philip Larkin are the focus of this investigation(1922-1985). The scholar is drawn to the poem because it addresses the universal but tragic issue of lifeand death in a methodical, tried-and-true format. The purpose of this study is to investigate the sourcesof pessimism and the possible explanations for Larkin’s out-of-the-ordinary views on the contemporaryworld. Most of his poetry reflect his sense of helplessness in the face of mortality. His dark poetry evokefeelings of illness, hopelessness, and the unpredictability of existence. His poetry on the subject ofdeath are very moving and make us consider the darker side of existence. The loss of his father reallyaffects him, and death is a recurring theme in many of his poetry. The purpose of this study is toinvestigate the causes of pessimism and the possible justifications for Larkin’s out-of-the-ordinary viewson the contemporary world. The poems selected for this article do an excellent job of reflecting this.